المسؤولية بسبب الامتناع عن تنفيذ القرارات القضائية الإدارية والجزاءات المترتبة عنها - شرون, حسينة (revue mofakir, 2018)
المسؤولية بسبب الامتناع عن تنفيذ القرارات القضائية الإدارية والجزاءات المترتبة عنها